The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1002/humu.23759
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of CEP250 variant identified in nonsyndromic retinitis pigmentosa

Abstract: Retinitis pigmentosa (RP) is the most common manifestation of inherited retinal diseases with high degree of genetic, allelic, and phenotypic heterogeneity. CEP250 encodes the C‐Nap1 protein and has been associated with various retinal phenotypes. Here, we report the identification of a mutation (c.562C>T, p.R188*) in the CEP250 in a consanguineous family with nonsyndromic RP. To gain insights into the molecular pathomechanism underlying CEP250 defects and the functional relevance of CEP250 variants in huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“…Firstly, no functional genomics studies were performed in the present study. Experimental validations are essential to determine if interesting variants are indeed responsible for clinical symptoms [50,51]. For example, a recent study demonstrates the rare variants of ABCG2 at both the clinical level and the functional level by complex approach [52].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, no functional genomics studies were performed in the present study. Experimental validations are essential to determine if interesting variants are indeed responsible for clinical symptoms [50,51]. For example, a recent study demonstrates the rare variants of ABCG2 at both the clinical level and the functional level by complex approach [52].…”
Section: Discussionmentioning
confidence: 99%
“…A previous complex segregation and linkage analysis of familial gout revealed an autosomal-arbitrary major gene model (20). WES is able to provide insights into the pathogeny of hereditary diseases and extend molecular diagnosis (45)(46)(47)(48). Therefore, WES was performed in three families with gout.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, we employed the targeted nextgeneration sequencing method to test all of the known skeletal, muscle, and nervous system monogenic diseases, and used PCR to verify the mutation sites of the family. The next-generation sequencing method has proven to be a very powerful approach to identify mutations for rare diseases (Huang et al, 2018(Huang et al, , 2019. The sequencing results showed that the patient had compound heterozygous mutations of p.S79L (c.236C > T) and p.T489S (c.1466C > G).…”
Section: Discussionmentioning
confidence: 99%